Social Sciences and the Meaning of Teaching Them. Interview with Dr. Isabelino Siede - Ramos Torres, Yeimer (2025)
This interview explores the purposes and challenges of teaching Social Sciences in primary and secondary education. Dr. Isabelino Siede analyzes the historical transition from training focused on national identity and "patriotic catechism" toward a pedagogy that promotes critical thinking. The dialogue emphasizes the importance of problematizing content through questions that invite students to doubt, investigate, and confront common sense with scientific rigor. It concludes that teaching Social Sciences involves not only transmitting disciplinary findings but also the procedures and ways of thinking that allow for an understanding of social reality as an object in constant movement and dispute.